PEMBERDAYAAN USAHA TEPUNG TAPIOKA GUNA MENINGKATKAN PENDAPATAN KELUARGA DI KECAMATAN AMBULU - Dwi Perwitasari Wiryaningtyas; Luckman Ashary (INTEGRITAS : Jurnal Pengabdian, 2017)
This program aims to improve the entrepreneurship spirit of the society through the establishment of a group of joint ventures and empower the potential of the society in increasing the family's income through the increase of productive economic enterprises. So far, most of the cassava harvest is sold in fresh and raw form so that the income is less than optimal. Based on the results of identification and discussion with the partners, it was agreed that the society needs knowledge about the processing of cassava into potential processed products, namely tapioca flour to increase income. There are two solutions offered for partners, namely the enhancement of partner knowledge on how to manufacture tapioca starch and counseling and training of tapioca starch making technology. Evaluation is done by giving pretest and post test to partners. The average difference between pretest and post test values was a large increase in participants' knowledge. Evaluation of participant's skills was assessed as the participants perform the summed practice with the data values of the participant record. The results showed that there was an increase of 99.5% of participants' knowledge. In addition, the evaluation of participants' skills in making tapioca flour was categorized as good (Group I got an average of 3.8 and Group II got an average of 4.15)